Validation of an instrument to measure treatment adherence in hypertension and diabetes - Romero Guevara, Sandra Lucrecia; Parra, Dora Inés; Roa Díaz, Zayne Milena; Rojas, Lyda Z. (Revista Cuidarte, 2020)
Introduction: Hypertension and diabetes mellitus are chronic diseases imposing a significant economic and social burden. Managing these diseases requires lifestyle changes, adherence to drug treatment and effective disease monitoring. Measuring compliance usually focuses on drug treatment, leaving aside the comprehensive approach which involves different key recommendations for appropriate control of these diseases. Objective: To determine the construct and reproducibility validity of the Nursing Outcomes Classification label “Therapeutic behavior: illness or injury (1609)” to measure adherence to the therapeutic regimen in people with hypertension and type 2 diabetes mellitus. Materials and Methods: A cross-sectional study was conducted among 500 users of cardiovascular risk reduction programs in Bucaramanga, Colombia. An instrument was designed to measure adherence to treatment based on the Nursing Outcomes Classification taxonomy, current recommendations from scientific literature and researchers experience. Construct validity was assessed using a principal component factor analysis based on the Rasch model. Reproducibility was validated using the intraclass correlation coefficient in 100 users. Results: A 13-item instrument comprising 5 indicators of the Nursing Outcome Classification label (1609) was developed, which explained 67.62% of the total variation, fitting the Rasch model (unidimensionality of the adherence construct). Reproducibility was 0.63 (95% CI 0.46-0.75). Conclusions: Evidence was found for the construct validity of the instrument operationalizing the Nursing Outcomes Classification label (1906) for the measurement of adherence to the therapeutic regimen in patients with hypertension and diabetes.How to cite this article: Romero Guevara  Sandra Lucrecia, Parra Dora Inés, Roa Díaz Zayne Milena, Rojas Lyda Z. Validación de un instrumento para medir la adherencia al tratamiento en hipertensión y diabetes. Revista Cuidarte. 2020;11(3):e1062. http://dx.doi.org/10.15649/cuidarte.1062
Keywords: Validation Studies; Surveys and Questionnaires; Standardized Nursing Terminology; Treatment Adherence and Compliance; Hypertension; Diabetes Mellitus, Type 2